Origin of hydrogen evolution activity on MS2 (M = Mo or Nb) monolayers1. Issue 37 (7th October 2015) - Chen, Xiaobo; Gu, Yu; Tao, Guohua; Pei, Yanli; Wang, Guangjin; Cui, Ni
<x xml:space="preserve">Abstract</x> The Volmer reaction is thermodynamically governed by adiabatic electron and proton affinities, and the high HER activity of 2D MS2 monolayers comes from their large adiabatic electron affinities.